Do health literacy and awareness of polycystic ovary syndrome predict the lifestyle choices of Arabic-speaking female university students - Reham Al Maamari; Iman Al Hashmi; Al Anoud Al Dhuli; Ashjan Al Abri; Asma Al Ghaithi; Sakeena Al Sinan (Wolters Kluwer Medknow Publications, 2023)
Background: Considering the increasing prevalence of Polycystic Ovarian Syndrome (PCOS) and its related complications-such as obesity, cardiovascular diseases, and infertility-in the Middle East, it is imperative to create sufficient public awareness about this issue. Accordingly, the potential link between PCOS awareness and health literacy level with the lifestyle choices of Arabic-speaking female university students was examined in this cross-sectional study. Materials and Methods: This research was conducted in the Sultanate of Oman and involved 446 Arabic-speaking female university students, who completed a self-administered online questionnaire, Single Item Literacy Screener, and PCOS Awareness Tool. Results: The findings showed that, while 53.50% of the study participants had inadequate health literacy, 79.80% demonstrated an acceptable level of PCOS awareness. However, this did not seem to influence their lifestyle, given that 59.20% of the respondents were physically inactive and 83.30% regularly consumed fast food. Regression analysis results nonetheless revealed that health literacy and PCOS awareness were significant predictors of lifestyle choices (F2,44 = 5.98, p < 0.05, 95% CI [4.44-5.35]). Conclusions: The Arabic-speaking female university students' health literacy level and PCOS awareness are significant predictors of their lifestyle choices. Thus, the policymakers in the Arab region need to develop effective strategies aimed at PCOS prevention, focusing specifically on raising public awareness about PCOS and its negative consequences on female reproductive health. In addition, university administrators should ensure the availability of healthy food choices at their campuses as well as opportunities for physical activity to promote healthy lifestyle among all students.